Highlight of Immune Pathogenic Response and Hematopathologic Effect in SARS-CoV, MERS-CoV, and SARS-Cov-2 Infection - Liang, Yanwen; Wang, Mong-Lien; Chien, Chian-Shiu; Yarmishyn, Aliaksandr A.; Yang, Yi-Ping; Lai, Wei-Yi; Luo, Yung-Hung; Lin, Yi-Tsung; Chen, Yann-Jang; Chang, Pei-Ching; Chiou, Shih-Hwa (Frontiers in Immunology, 2020)
A sudden outbreak of COVID-19 caused by a novel coronavirus, SARS-CoV-2, in Wuhan, China in December 2019 quickly grew into a global pandemic, putting at risk not only the global healthcare system, but also the world economy. As the disease continues to spread rapidly, development of prophylactic and therapeutic approaches is urgently required. Although some progress has been made in understanding the viral structure and invasion mechanism of coronaviruses that may cause severe syndrome, due to the limited understanding of the immune effects caused by SARS-CoV-2, it is difficult for us to prevent patients from developing the acute respiratory distress syndrome (ARDS) and pulmonary fibrosis (PF), the major complications of coronavirus infection. Therefore, any potential treatments should focus not only on direct killing of coronaviruses and prevention strategies by vaccine development, but also on keeping in check the acute immune/inflammatory responses, resulting in ARDS and PF. In addition, potential treatments currently under clinical trials focusing on killing coronaviruses or vaccine preventing coronavirus infection largely ignore the host immune response. However, taking care of SARS-CoV-2 infected patients with ARDS with PF is considered to be the major difficulty. Therefore, further understanding of the host immune response to SARS-CoV-2 is extremely important for clinical resolution and saving medication cost. In addition to briefly overview of the structure, infection mechanism and possible therapeutic approaches, we summarized and compared the hematopathologic effect and immune responses to SARS-CoV, MERS-CoV, and SARS-CoV-2. The indirect immune response caused by SARS and direct infection, replication and destroying immune cells by MERS-CoV. The molecular mechanisms of SARS-CoV and MERS-CoV infection induced lymphopenia or cytokine storm may bring us some hint to fight towards SARS-CoV-2, the novel coronavirus. This may provide clue of using immune therapy as combine treatment to prevent the patient develop into severe respiratory syndrome and largely reduced complications.